PENINGKATAN PENGETAHUAN DAN SIKAP KELUARGA PASIEN STROKE MELALU VIDEO MIRROR THERAPY: PROMOSI KESEHATAN BERBASIS SELF CARE - Sodikin, Sodikin (Jurnal Kesehatan Madani Medika, 2025)
Mirror therapy videos have proven to be an effective health education medium for improving the knowledge and attitudes of stroke patients' families regarding home-based care. This study aims to evaluate the extent to which mirror therapy videos, compared to pamphlets, influence the understanding and attitudes of families toward stroke care. The research used a quasi-experimental design with two groups, each consisting of 15 respondents: one group received education through mirror therapy videos, while the other received pamphlets. Data were collected using questionnaires and analyzed using an independent sample t-test. The results showed that the video group had a higher average knowledge score (10.13) and attitude score (31.33) compared to the pamphlet group (knowledge: 8.80, attitude: 29.27). Statistical tests revealed significant differences between the two groups, with p-values of 0.044 for knowledge and 0.047 for attitude (p < 0.05). This study concludes that mirror therapy videos are more effective than pamphlets in enhancing the knowledge and attitudes of stroke patients' families, and are therefore recommended as a primary educational medium for home stroke care.